ENT 530 Social Media Portfolio / Mohamad Zailani Sapari - Sapari, Mohamad Zailani (2019)
For this project, I choose to set up a business which is selling hoodie and sweatshirt. This business is managed and also owned by me. This business is officially started on 301h September 2019 and located at No 59, Kampung Parit Lapis Mahang, 83200, Senggarang Batu Pahat, Johor. I would search for the order made by the customer and ship it ou to them as fast as possible.